Researching worthwhile performance enhancements - Hopkins, W. G.; Hawley, J. A.; Burke, L. M. (Sportscience, 1999)
For an athlete at the top of the field, a performance enhancement makes a difference to the chance of winning when it is about half the athlete's typical between-event variation in performance. Measuring enhancements of this magnitude with adequate precision requires much bigger sample sizes than researchers normally use. To avoid confusion over interpretation of their findings, researchers should therefore publish and explain the precision of their estimates of performance enhancement.